Влияние гидравлического подпора на осевую нагрузку - Кожевников, А.А.; Кузин, Ю.Л.; Гриняк, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The change of hydraulic pressure in connection with the increase of thickness of wall of boring column in lower part is considered. The analysis of formula showed that constituent from the difference of areas of column and boring pipes represents insignificant part.